WAYS TO IMPROVE POSTOPERATIVE WOUND HEALING IN THE SURGICAL TREATMENT OF LOCALLY ADVANCED TUMORS OF THE HEAD AND NECK - I. L. Kiselev; V. V. Khvostovoy; Yu. S. Vorona; V. E. Romanishchev; I. S. Vorona (Опухоли головы и шеи, 2015)
The paper deals with the prevention of suture failure after surgery for locally advanced malignancies of the head and neck. According to the data of different authors, postoperative festering wounds may be noted in 40–60 % of patients and persistent pharyngeal defects are seen in 10–35 % of cases. The efficacy of applying rich-enriched autoplasma membranes to the suture area is clinically evaluated. Platelets are known to be the most convenient and inexpensive source of proteins, the growth factors involved in the regeneration of affected tissues. The experience in their use in dentistry, cardiovascular surgery, and traumatology is richest. The above properties of platelets are a theoretical premise for their employment when forming a pharyngeal suture to enhance its stability.